Proceedings of the 12th ACM/IEEE-CS Joint Conference on Digital Libraries 2012
DOI: 10.1145/2232817.2232821
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing digital collections at archive-it

Abstract: Archive-It, a subscription service from the Internet Archive, allows users to create, maintain and view digital collections of web resources. The current interface of Archive-It is largely text-based, supporting drill-down navigation using lists of URIs. To provide an overview of each collection and highlight the collection's underlying characteristics, we present four alternate visualizations (image plot with histogram, wordle, bubble chart and timeline). The sites in an Archive-It collection may be organized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The authors connect heterogeneous digital collections through the temporal references found in the documents as well as their textual content, in order to support scholars to detect, visualize, and explore materials from different perspectives. Padia et al [15] provided an overview of a web archive collection by highlighting the collection's underlying characteristics using different visualizations of image plots, wordle, bubble charts, and timelines. Lin et al [10] present an interactive visualization based on topic models for exploring archived content, so that users can get an overview of the collection content.…”
Section: Related Workmentioning
confidence: 99%
“…The authors connect heterogeneous digital collections through the temporal references found in the documents as well as their textual content, in order to support scholars to detect, visualize, and explore materials from different perspectives. Padia et al [15] provided an overview of a web archive collection by highlighting the collection's underlying characteristics using different visualizations of image plots, wordle, bubble charts, and timelines. Lin et al [10] present an interactive visualization based on topic models for exploring archived content, so that users can get an overview of the collection content.…”
Section: Related Workmentioning
confidence: 99%
“…al. [16] provide an overview of a web archive collection by highlighting the collection's underlying characteristics using different visualizations of image plots, wordle, bubble charts and timelines. Lin et.…”
Section: Related Workmentioning
confidence: 99%
“…They provide aids in uncovering important relationships of searched results or entities, cues for filtering of information, and assistance to identify specific patterns of search results (Kwon et al 2012). They've been used to explore temporal metadata and relationships in digital libraries (Kumar et al 1998), visually browse and explore a blog archive by using a time slider (Indratmo et al 2008), visualize email archive content (Viegas et al 2006), visualize distributed software development consisting of code repositories and project communication (Gilbert and Karahalios 2007), explore temporal patterns of events within medical histories (Fails et al 2006), visualize digital collections of web resources (Padia et al 2012) and visualize design process with evolving building information data (Kim et al 2011), among other examples. Timelines can also be used as an interactive filter for information indexed by time (e.g., Wu and Tory 2009;Jones et al 2013).…”
Section: Timeline-based Visualizationsmentioning
confidence: 99%